Enrollment volume effect on risk factor control and outcomes in the SAMMPRIS trial. (15th December 2015) - Chiu, David; Klucznik, Richard P.; Turan, Tanya N.; Lynn, Michael J.; McCane, Charles D.; Katz, Lawrence B.; Nizam, Azhar; Derdeyn, Colin P.; Fiorella, David; Lane, Bethany F.; Montgomery, Jean; Janis, Scott; et al.
Abstract : Objective: The role of physician experience and patient volumes on the outcome of surgical or endovascular procedures has been well-studied but there are limited data on how these factors affect the outcome of medical therapy. Methods: In the stenting and medical cohorts of the Stenting and Aggressive Medical Management for the Prevention of Recurrent Ischemic Stroke (SAMMPRIS) trial, we compared Kaplan-Meier (K-M) curves for the primary endpoint (any stroke or death within 30 days of enrollment or ischemic stroke in the territory beyond 30 days) using the log-rank test and the percentages of patients achieving target levels for primary and secondary risk factors during the study using Fisher exact test between patients at high-enrolling (≥12 patients) vs low-enrolling (<12 patients) sites. Results: In the stenting group, the K-M curves for the primary endpoint were similar at high-enrolling sites and low-enrolling sites ( p = 0.93) with rates of 13.5% vs 14.7% at 30 days and 19.0% vs 20.6% at 2 years. In the medical group, the K-M curves differed between high-enrolling sites and low-enrolling sites ( p = 0.0005) with rates of 1.8% vs 9.8% at 30 days and 7.3% vs 20.9% at 2 years. The percentages of patients who achieved targets for low-density lipoprotein cholesterol and systolic blood pressure at high- vs low-enrolling sites in both treatment groups combined were 64% vs 49% ( p = 0.003) and 70% vs 59% ( p = 0.026), respectively. Conclusions: High-enrolling sites in SAMMPRIS achieved better control of primary risk factors and much lower rates of the primary endpoint than low-enrolling sites in the medical group, suggesting that experience with medical management is an important determinant of patient outcome.